Autobiographical Elements and Dreams in Jane Eyre and Agnes Grey - Kondor Veronika; Csetényi Korinna (2000)
In this thesis an attempt will be made to prove that both Charlotte and Anne Bront6, used autobiographical elements in their works and while doing so they wrote about their dreams that they could never fulfil. In the introduction the poor prospects of a woman in the Victorian era will be introduced first in general, then more specifically in the case of the sisters. In the first chapter some pieces of information will be written about both Haworth, the place they lived in and the Brontó family. The next chapter is going to contain the description of Anne's character, her life as a governess and the examination of one of her novel, Agnes Grey. It is followed by a chapter about Charlotte's personality, about her activity as a governess and as a teacher, a short summary about her journey to Brussels and the interpretation of her most famous novel, Jane Eyre. Both in the second and the third chapters the love in the authors' lives will be depicted. In the fourth chapter some similarities and differences between the authors and the above mentioned novels will be pointed out. The aim of this thesis is to depict the authors' lives and to show, through their novels, that they lived unhappily and unlike their fictional characters, they could never fulfil their dreams.
Keywords: Pedagógusképzés